Robotics Research The 15th International Symposium ISRR - Christensen, Henrik I.; Khatib, Oussama; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume presents a collection of papers presented at the 15th International Symposium of Robotic Research (ISRR). ISRR is the biennial meeting of the International Foundation of Robotic Research (IFRR) and its 15th edition took place in Flagstaff, Arizona on December 9 to December 12, 2011. As for the previous symposia, ISRR 2011 followed up on the successful concept of a mixture of invited contributions and open submissions. Therefore approximately half of the 37 contributions were invited contributions from outstanding researchers selected by the IFRR officers and the program committee, and the other half were chosen among the open submissions after peer review. This selection process resulted in a truly excellent technical program which featured some of the very best of robotic research. The program was organized around oral presentation in a single-track format and included for the first time a small number of interactive presentations. The symposium contributions contained in this volume report on a variety of new robotics research results covering a broad spectrum including perception, manipulation, grasping, vehicles and design, navigation, control and integration, estimation and SLAM. .
Aerial Vehicles progress On Pico Air Vehicles -- Perception and Mapping -- Planning -- Systems and Integration -- Control.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Control, Robotics, Automation; Artificial Intelligence